Effect of mesh on CFD aerodynamic performances of a container ship - He, Ngo Van; Thai, Le Thi (Vietnam Journal of Marine Science and Technology, 2020)
In this paper, a commercial CFD code, ANSYS-Fluent has been used to investigate the effect of mesh number generated in the computed domain on the CFD aerodynamic performances of a container ship. A full-scale model of the 1200TEU container ship has been chosen as a reference model in the computation. Five different mesh numbers for the same dimension domain have been used and the CFD aerodynamic performances of the above water surface hull of the ship have been shown. The obtained CFD results show a remarkable effect of mesh number on aerodynamic performances of the ship and the mesh convergence has been found. The study is an evidence to prove that the mesh number has affected the CFD results in general and the accuracy of the CFD aerodynamic performances in particular.